2013
DOI: 10.1002/dvg.22735
|View full text |Cite
|
Sign up to set email alerts
|

Recent structural and functional insights into the family of sodium calcium exchangers

Abstract: Maintenance of calcium homeostasis is necessary for the development and survival of all animals. Calcium ions modulate excitability and bind effectors capable of initiating many processes such as muscular contraction and neurotransmission. However, excessive amounts of calcium in the cytosol or within intracellular calcium stores can trigger apoptotic pathways in cells that have been implicated in cardiac and neuronal pathologies. Accordingly, it is critical for cells to rapidly and effectively regulate calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 107 publications
0
31
0
Order By: Relevance
“…Although Ca 2+ release from intracellular stores is a key event in the transduction pathway of the response, the development and stability of the vasodilation depends on the Ca 2+ influx phase, which has been mainly attributed to capacitative Ca 2+ entry (27, 28). However, NCX has also been found to contribute to the rise of [Ca 2+ ] i in different cell types (9, 17). It is well‐accepted that NCX‐mediated Ca 2+ extrusion has an important role in the control of [Ca 2+ ] i in endothelial cells (11, 12, 27), but the exchanger may also transport Ca 2+ into the cell by the activation of the reverse mode (1 Ca 2+ in/3 Na + out) (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Ca 2+ release from intracellular stores is a key event in the transduction pathway of the response, the development and stability of the vasodilation depends on the Ca 2+ influx phase, which has been mainly attributed to capacitative Ca 2+ entry (27, 28). However, NCX has also been found to contribute to the rise of [Ca 2+ ] i in different cell types (9, 17). It is well‐accepted that NCX‐mediated Ca 2+ extrusion has an important role in the control of [Ca 2+ ] i in endothelial cells (11, 12, 27), but the exchanger may also transport Ca 2+ into the cell by the activation of the reverse mode (1 Ca 2+ in/3 Na + out) (9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the participation of NCX in endothelium‐dependent, Ca 2+ ‐mediated responses has not, to our knowledge, been evaluated in resistance arteries. Of the 3 isoforms of NCX (NCX1, NCX2, and NCX3) (16, 17), endothelial cells only express NCX1 (16) and, in porcine aortic endothelial cells, that isoform was found to be localized in the signaling microdomains known as caveolae (14). That particular subcellular localization may place the exchanger in a tight spatial, and probably, functional association with many important Ca 2+ ‐dependent signaling proteins, such as eNOS and SK Ca , which are also found in the caveolae (18, 19).…”
mentioning
confidence: 99%
“…NCX1 is expressed in heart, brain, bladder, kidney, and cells of the enamel organ; NCX2 is expressed in brain and skeletal muscle; and NCX3 is expressed in brain, skeletal muscle and cells of the enamel organ (Lytton, 2007; Okumura et al, 2010; Lacruz et al, 2012b; Sharma and O'halloran, 2014). Okumura et al demonstrated NCX1 and NCX3 expression at the apical pole of both secretory and maturation ameloblasts, and expression of NCX1 was also observed in cells of the stratum intermedium and papillary layer (Okumura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NCKX4 is expressed in olfactory neurons (Stephan et al, 2011), and also in the maturation-stage ameloblasts (Hu et al, 2012). NCKX5 is expressed in skin melanocytes, retinal epithelium, and brain (Schnetkamp, 2004; Lytton, 2007; Sharma and O'halloran, 2014; Jalloul et al, 2016a,b). NCKX6/NCLX was originally considered a member of the NCKX family but is now considered part of the Ca 2+ cation (CCX) exchanger branch (Cai and Lytton, 2004; Sharma and O'halloran, 2014) as a mitochondrial membrane Ca 2+ , Li + /Na + exchanger with a wide tissue distribution (Schnetkamp, 2004; Lytton, 2007; Sharma and O'halloran, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All three isoforms have similar properties (17,26), but the isoform-specific distribution in different brain regions, cell types and subcellular localization (38, 43; for review see ref. 40) suggests distinct functions for different isoforms. For examples, knockouts of NCX specific isoforms have revealed differential roles of NCX2 and NCX3 in the regulation of presynaptic and postsynaptic [Ca 2+ ] i in the mouse CA1 hippocampal neurons (18,31).…”
Section: Introductionmentioning
confidence: 99%